Violence: An Unavoidable Condition of human existence (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Though all these representations of violence, communalism is established as a fact that leads to dehumanization, shrinkages of human sympathies and snapping of meaningful communication between the people. They recognize it as a brute force that created disjunction between passion and reason, between man and society, man and nature, and man and civilization. However, in most of these writers, these features of communalism get delineated more as descriptive set-pieces than as consciously and analytically thought of manifestations. Despite the dialectical nature of violence and its representation through the binary structures, yielding multiplicity of analyses and arguments about violence, it is believed that creative effort of each writer was underlain by one single motif, that is, to expose and lay bare the subterfuges of human nature and project them on to the world of fiction. This implication of vital human significance has lent a universal appeal to the Indo- English fiction of partition violence and it is this that is proposed as the subject of investigation in the subsequent section.